According to Vieta's Formulas, if
![x_1,x_2](https://tex.z-dn.net/?f=x_1%2Cx_2)
are solutions of a given quadratic equation:
Then:![a(x-x_1)(x-x_2)](https://tex.z-dn.net/?f=a%28x-x_1%29%28x-x_2%29)
is the completely factored form of
![ax^2+bx+c](https://tex.z-dn.net/?f=ax%5E2%2Bbx%2Bc)
.
If choose
![x=d^2](https://tex.z-dn.net/?f=x%3Dd%5E2)
, then:
![\displaystyle x^2-8x+16=0\\\\x_{1,2}= \frac{8\pm \sqrt{64-64} }{2}=4](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%5E2-8x%2B16%3D0%5C%5C%5C%5Cx_%7B1%2C2%7D%3D%20%5Cfrac%7B8%5Cpm%20%20%5Csqrt%7B64-64%7D%20%7D%7B2%7D%3D4%20)
So, according to Vieta's formula, we can get:
![x^2-8x+16=(x-4)(x-4)= (x-4)^2](https://tex.z-dn.net/?f=x%5E2-8x%2B16%3D%28x-4%29%28x-4%29%3D%20%28x-4%29%5E2)
But
![x=d^2](https://tex.z-dn.net/?f=x%3Dd%5E2)
:
Answer:
do not sell them
Step-by-step explanation:
bc i alredy did
The question is incomplete:
If you see that gasoline costs $1.70 in Georgia and $3.40 in California, you can conclude that gasoline is twice as expensive in California as in Georgia. This conclusion from this comparison reflects the function of money as a:
-store of value
-an object with a value that varies sharply from one place to another
-medium of exchange
-unit of account
Answer:
Unit of account
Step-by-step explanation:
-Store of value refers to something that can be kept for a period of time and maintains its value in the future.
-An object with a value that varies sharply from one place to another means that products can have different prices in different places.
-Medium of exchange refers to an object with an standard value that allows you to purchase goods or services.
-Unit of account refers to a numerical unit that allows you to compare the value of products and services.
According to this, the answer is that this conclusion from this comparison reflects the function of money as a unit of account because it indicates that money works as a unit that you can use to compare the value of products, in this case the price of gasoline in different places.
Answer: x=−3
Step-by-step explanation: Let's solve your equation step-by-step.
2
3
(3x+9)=−2(2x+6)
Step 1: Simplify both sides of the equation.
2
3
(3x+9)=−2(2x+6)
(
2
3
)(3x)+(
2
3
)(9)=(−2)(2x)+(−2)(6)(Distribute)
2x+6=−4x+−12
2x+6=−4x−12
Step 2: Add 4x to both sides.
2x+6+4x=−4x−12+4x
6x+6=−12
Step 3: Subtract 6 from both sides.
6x+6−6=−12−6
6x=−18
Step 4: Divide both sides by 6.
6x
6
=
−18
6
x=−3
Step-by-step explanation:
I think your answer is 3
....